2019
DOI: 10.1158/0008-5472.can-19-0063
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of HSF1 by PIM2 Induces PD-L1 Expression and Promotes Tumor Growth in Breast Cancer

Abstract: Heat shock transcription factor 1 (HSF1) is the master regulator of the proteotoxic stress response, which plays a key role in breast cancer tumorigenesis. However, the mechanisms underlying regulation of HSF1 protein stability are still unclear. Here, we show that HSF1 protein stability is regulated by PIM2-mediated phosphorylation of HSF1 at Thr120, which disrupts the binding of HSF1 to the E3 ubiquitin ligase FBXW7. In addition, HSF1 Thr120 phosphorylation promoted proteostasis and carboplatin-induced autop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 45 publications
0
53
0
Order By: Relevance
“…Taken together, β-catenin suppressed the biogenesis of miR455-3p to allow METTL3 binding for m6A modification of HSF1 mRNA, thus stimulating HSF1 mRNA translation. In cancer cells, HSF1 can drive a transcriptional program distinct from heat shock response to support malignant phenotypes [ 15 , 43 ]. For instance, HSF1 can drive the transcription of PDK3 (Pyruvate Dehydrogenase Kinase 3) to promote glycolysis in chemo-resistant cancer cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, β-catenin suppressed the biogenesis of miR455-3p to allow METTL3 binding for m6A modification of HSF1 mRNA, thus stimulating HSF1 mRNA translation. In cancer cells, HSF1 can drive a transcriptional program distinct from heat shock response to support malignant phenotypes [ 15 , 43 ]. For instance, HSF1 can drive the transcription of PDK3 (Pyruvate Dehydrogenase Kinase 3) to promote glycolysis in chemo-resistant cancer cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that the phosphorylation of HSF1 by PIM2, which interrupts the binding of the E3 ligase to HSF1, enhances the stability of HSF1, and promotes HSF1 binding to PD-L1 promoter. The resulting overexpression of PD-L1 enhances the breast cancer growth and tumorigenesis in vitro and in vivo [89]. In addition, Family with sequence similarity member C (FAM3C) is a commonly known interleukin-like EMT inducer, and it has been demonstrated that the upregulation of HSF1 is the underlying mechanism of FAM3C-mediated tumorigenesis [90].…”
Section: Role Of Hsf1 In Cancer Developmentmentioning
confidence: 99%
“…The beads were washed at least 5 times using IP buffer, and then used for subsequent experiments. The indicated proteins were expressed in E.coli BL21 (DE3), and GST-pull down assay was performed as described previously 17 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, various special inhibitors, including JP11646, SMI-4a and SGI-1776, have been developed for PIM kinase activity and have been used for clinical treatment 19 - 21 . Recently, we found that PIM2 acts as an oncogene in breast cancer 15 , 17 , 22 , but the underlying mechanism of its oncogene function remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%